Dynamic control of nucleic-acid-sensing Toll-like receptors by the endosomal compartment. (5th July 2021) - Miyake, Kensuke; Saitoh, Shin-Ichiroh; Fukui, Ryutaro; Shibata, Takuma; Sato, Ryota; Murakami, Yusuke
Abstract: Nucleic-acid (NA)-sensing Toll-like receptors (TLRs) are synthesized in the endoplasmic reticulum and mature with chaperones, such as Unc93B1 and the protein associated with TLR4 A (PRAT4A)–gp96 complex. The TLR–Unc93B1 complexes move to the endosomal compartment, where proteases such as cathepsins activate their responsiveness through proteolytic cleavage of the extracellular domain of TLRs. Without proteolytic cleavage, ligand-dependent dimerization of NA-sensing TLRs is prevented by the uncleaved loop in the extracellular domains. Additionally, the association of Unc93B1 inhibits ligand-dependent dimerization of TLR3 and TLR9 and, therefore, Unc93B1 is released from these TLRs before dimerization. Ligand-activated NA-sensing TLRs induce the production of pro-inflammatory cytokines and act on the endosomal compartment to initiate anterograde trafficking to the cell periphery for type I interferon production. In the endosomal compartment, DNA and RNA are degraded by DNases and RNases, respectively, generating degradation products. DNase 2A and RNase T2 generate ligands for TLR9 and TLR8, respectively. In this mechanism, DNases and RNases control innate immune responses to NAs in endosomal compartments. NA-sensing TLRs and the endosomal compartment work together to monitor environmental cues through endosomes and decide to launch innate immune responses.